Diagnostic and prognostic implications of right ventricular-arterial coupling in cardiac amyloidosis and in genetic and non-genetic cardiomyopathies with hypertrophic phenotype. (4th February 2022) - Palmiero, G; Rubino, M; Monda, E; Lioncino, M; Verrillo, F; Dongiglio, F; Caiazza, M; Vetrano, E; Cirillo, A; Fusco, A; Ascione, L; Caso, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND & PURPOSE. Right ventricular (RV) dysfunction in cardiomyopathies is a consequence of chronic overload (i.e. aortic stenosis, AS) or direct involvement of systemic disorders (i.e. cardiac amyloidosis, CA). The Tricuspid Annular Plane Systolic Excursion/Systolic Pulmonary Artery Pressure (TAPSE/sPAP) ratio has been recently proposed as a surrogate of RV-arterial coupling (RVAC). This study aims to compare RVAC between CA subgroups and between CA and other forms of genetic and non-genetic cardiomyopathies with hypertrophic phenotype. METHODS. We enrolled 50 patients with CA (26 AL and 24 wtATTR) and 75 cardiomyopathies with hypertrophy phenotype (LVH group) [25 pts with hypertrophic cardiomyopathy (HCM), 25 hypertensive pts(HypCM), and 25 pts with AS]. Besides routine echocardiographic measurements, we analysed right chambers dimensions and classical and novel parameters of RV function [TAPSE, TAPSE/sPAP, St wave, global (RVGLS) and free-wall (RVFWS) strain]. RESULTS. Compared to AL, the ATTR group showed higher right chambers dimensions, without differences in all RV systolic parameters. Compared to the LVH group, CA patients showed no differences in RV dimensions while RV systolic parameters, including the TAPSE/sPAP ratio, were significantly reduced in the presence of significantly higher LV filling pressures. At ROC curve analysis, TAPSE (AUC 0.877; 95% CI: 0.811-0.943; p < 0, 0001) and TAPSE/sPAP ratio (AUC 0.859; 95% CI: 0.783-0.935; p < 0, 0001) showed the best ability in discriminating CA among other forms of LVH (cut-off 20.5 mm for TAPSE with sensibility of 80.5% and specificity of 78.8%, respectively; cut-off 0.62 for TAPSE/sPAP ratio with sensibility of 85.4% and specificity 81.8%). At 24 months follow-up, there were 15 deaths in CA (30%) and 4 in LVH group (5%). At Kaplan-Meier estimation, the TAPSE/sPAP ratio showed progressively a significantly reduced survival in the lowest interquartile ranges. Moreover, at multivariate analysis, TAPSE/sPAP was the only independent prognostic factor (β -5, 644; 95% IC: 0, 000-0, 522; p < 0, 027). CONCLUSIONS. The RVAC is significantly impaired in CA compared to the LVH group but not between CA subgroups. Its reduction seems attributable to both increase LV filling pressure, due to the restrictive nature of the infiltrative cardiomyopathy, and reduced RV systolic function, due to either indirect RV chronic overload and direct myocardial infiltration. The TAPSE/sPAP ratio is a surrogate of RVAC and proved to be a novel echocardiographic parameter useful in both discriminating CA among genetic and non-genetic forms of LVH, and stratifying the prognosis.